Hierarchical reinforcement of randomly-oriented carbon nanotube mats by ion irradiation. (April 2016) - Fornasiero, Francesco; LeBlanc, Mary; Charnvanichborikarn, Supakit; Kucheyev, Sergei O.; Shin, Swanee J.; Gong, Kuanping; Ci, Lijie; Park, Jinseong; Miles, Robin
Abstract: Because of their outstanding mechanical properties, carbon nanotubes (CNTs) are attractive 1-D nanoscale building blocks for lightweight composites that could potentially outperform naturally occurring materials. A still unsolved challenge for fully exploiting CNT superior mechanical properties for reinforcement of macroscopic systems is control of the interfacial interaction across multiple length scales to favor load transfer. Toward overcoming this challenge, we investigate here the effect of high-energy He + ion irradiation on the elastic modulus and tensile strength of thin films of randomly oriented double-walled nanotube (DWCNT) mats and DWCNT-epoxy composites. We correlate irradiation-induced reinforcement with the formation of cross-links at different hierarchical levels of the DWCNT network. Our measurements reveal a rapidly increasing reinforcement at low ion doses, attributed to intra-bundle CNT cross-links, followed by a slow mechanical reinforcement at higher doses, associated to inter-bundle cross-links. At the highest ion irradiation dose of this study, the strength and elastic modulus of DWCNT-epoxy composites approach ∼900 MPa and 25 GPa, respectively, which is among the best mechanical performances reported for randomly-oriented CNT mats. We also develop a model accounting for radiation-induced hierarchical reinforcement of DWCNT films. The model is in good agreement with the experimental results across the entire dose range.